Incidence of adverse events after discharge from a secondary hospital in northern Ghana - Iddrisu, Inusah D.; Anyanful, Akwasi; Nuvor, Samuel V. (International Journal Of Community Medicine And Public Health, 2019)
Background: Adverse events involve unintended injuries or complications resulting in death, disability, harm or prolonged hospital stay that arise from health care management. This paper aims at giving insight into the incidence, types and severity of adverse events after hospital discharge in the context of the management/care patients received from the hospital. Methods: A descriptive cohort study design was used in a secondary hospital in Ghana. The study population involved patients discharged from the medical, surgical and emergency wards of the Hospital. A total of 206 patients were recruited through a consecutive sampling technique. Results: The findings revealed an adverse events rate of 25.7%. The study also identified adverse events related to medications to be the leading type of adverse events recorded after discharge from the hospital. There were 3.9% death rate among participants 21 days after discharge from the hospital. The study revealed that adverse events usually occur after discharge from the hospitals which differ in several forms and in severity. Conclusions: These, therefore offer nurses and other service providers an opportunity to target the areas for improvement of services.